Preparation and characterization of New Phosphatic Derivatives of Synthetic Zeolite-4A provided by Indian Petrochemicals, Baroda - Banerjee, S.P.; Pimplapure, S. (Asian Journal of Chemistry, 2010)
Thermal behaviour of tri-cresyl phosphate (TCP) interacted Th(IV)-4A and TCP/4A have been investigated by TG-DTA up to 900ºC. The IR spectral studies confirm the interaction of TCP; crystalline nature of these derivatives has been investigated by XRD.